Analysis of Turkish 6/49 lottery results - Alper Vahaplar; Murat Erşen Berberler (MANAS: Journal of Engineering)
Turkish 6/49 Lottery is a chance game based on the selection of 6 of the 49 numbers by the draw machine, which has been of interest since the first day; such that statistics of this game, winning strategies, formulas etc., a number of popular books and newspaper articles have been published and some of the internet sites are now providing updated information to interested people; but a large part of these publications seem to be far from scientific point of view. In this study, all the draws in the past will be analyzed and the probability of being correctly guessed will be discussed by adhering to the theory of probability and statistical confidence tests.